Comparative selective pressure potential of antibiotics in the environment. (1st February 2023) - Emara, Yasmine; Jolliet, Olivier; Finkbeiner, Matthias; Heß, Stefanie; Kosnik, Marissa; Siegert, Marc-William; Fantke, Peter
Abstract: To guide both environmental and public health policy, it is important to assess the degree of antibiotic resistance selection pressure under measured environmental concentrations (MECs), and to compare the efficacy of different mitigation strategies to minimize the spread of resistance. To this end, the resistance selection and enrichment potential due to antibiotic emissions into the environment must be analysed from a life cycle perspective, for a wide range of antibiotics, and considering variations in the underlying fitness costs between different resistance mutations and genes. The aim of this study is to consistently derive fitness cost-dependent minimum selective concentrations (MSCs) from readily available bacterial inhibition data and to build MSC-based species sensitivity distributions (SSDs). These are then used to determine antibiotic-specific resistance selection concentrations predicted to promote resistance in 5% of exposed bacterial species ( R S C 5 ). Using a previously developed competition model, we provide estimated M S C 10 endpoints for 2, 984 antibiotic and bacterial species combinations; the largest set of modelled MSCs available to date. Based on constructed SSDs, we derive R S C 5 for 128 antibiotics with four orders of magnitude difference in their 'selective pressure potential' in the environment. By comparing our R S C 5 to MECs, we highlight specific environmental compartments (e.g. hospital and wastewater effluents, lakes and rivers), as well as several antibiotics (e.g. ciprofloxacin, norfloxacin, enrofloxacin, and tetracycline), to be scrutinized for their potential role in resistance selection and dissemination. In addition to enabling comparative risk screening of the selective pressure potential of multiple antibiotics, our SSD-derived R S C 5 provide the point of departure for calculating new life cycle-based characterization factors for antibiotics to compare mitigation strategies, thereby contributing towards a 'One-Health' approach to tackling the global antibiotic resistance crisis. Graphical abstract: Image 1 Highlights: Evidence on antibiotic resistance selection in the environment is mounting. We propose fitness cost-dependent minimum selective concentrations (MSC). Estimated MSC under a low-cost scenario for >2900 antibiotic-species combinations. Environmental resistance selection concentrations determined for 128 antibiotics. Selection potential in the environment identified.